OPINI MASYARAKAT MENGENAI HATE SPEECH PADA MEDIA MASSA TERHADAP ULAMA (Studi Kasus pada Masyarakat Meulaboh, Aceh Barat) - Siti Nurkhafifah Marisa; Rena Juliana; Reni Juliani (SOURCE : Jurnal Ilmu Komunikasi, 2021)
At present, there is much news of hate speech against ulama circulating in the mass media. Hate speech can have a negative impact on human relationships and between the religious communities developed to date. The purpose of this research is to discuss how the public opinion of Meulaboh presents to the mass media messages containing hate speech directed against ulama. This research used a qualitative approach by collecting data through interviews with 4 people from Meulaboh City and 2 lecturers of KPI STAIN Meulaboh. The results of this study show that having a huge impact on the news in the media for the community, especially the presence of gadgets, allows people to easily access a lot of the latest news. People who still hold strong religious values think the news is inappropriate. The news presented by the media is expected to be neutral and impartial, which can harm other parties.